Factors of resistance to progestin therapy in endometrial hyperplasia in women - Khaskhachikh , D.A.; Potapov , V.O.; Poslavska , O.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The article discusses endometrial hyperplasia (EH), a condition in which there is excessive proliferation of glandular and stromal components in the endometrium. EH is divided into atypical EH (simple or complex) and atypical EH (endometrioid intraepithelial neoplasia) based on the binary scoring system of WHO (2014). The risk of developing endometrial cancer (EC) in women with EH depends on several factors, including the type of EH, age, obesity, diabetes, and recurrent abnormal uterine bleeding. Currently, long-term cyclic progesterone therapy is an effective treatment for atypical EH, but ineffectiveness has been reported in some cases, and the reasons for this are not well understood. Objective. The purpose of the article is to investigate the possible causes of resistance of endometrial cells in its hyperplasia to progestin therapy and predict the effectiveness of therapy. Methods. The research uses methods of information-search, bibliographic and comparative analysis. Results. Elucidated causes and mechanisms of progesterone resistance in women with EH, such as genetic factors, hormonal factors, and epigenetic factors. The article emphasizes the need for additional research to understand the main mechanisms of resistance to progesterone therapy in EH. Conclusion. Resistance of endometrial hyperplasia to progestin therapy can be caused by various factors, such as hormone imbalance, abnormal expression of hormone receptors, gene mutations, dysfunction of the immune system, and others. Hormone receptors such as ER, PR and Ki-67 may play an important role in predicting endometrial resistance to progestins and in determining treatment approaches. Studies also show that abnormal expression of factors that control apoptosis, such as Caspase-3 and BAX, may be associated with endometrial resistance to progestins. In addition, disruption of E-cadherin expression can affect the development of endometrial hyperplasia and resistance to progestins. Therefore, the resistance of endometrial hyperplasia to progestin therapy is a complex problem, and more research is needed to understand the role of various factors in the development of this problem and to develop more effective treatment approaches.